Factors influencing physical and technical variability in the English Premier League - Bush, M. D.; Archer, D. T.; Hogg, R.; Bradley, P. S. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To investigate match-to-match variability of physical and technical performances in English Premier League players and quantify the influence of positional and contextual factors. Methods: Match data (N = 451) were collected using a multicamera computerized tracking system across multiple seasons (2005-06 to 2012-13). The coefficient of variation (CV) was calculated from match to match for physical and technical performances in selected positions across different match contexts (location, standard, and result). Results: Wide midfielders demonstrated the greatest CVs for total distance (4.9% ± 5.9%) and central midfielders the smallest (3.6 % +/- 2.0%); nevertheless, all positions exhibited CVs <5% (P > .05, effect size [ES] 0.1-0.3). Central defenders demonstrated the greatest CVs and wide midfielders the lowest for both high-intensity running (20.2% ± 8.8% and 13.7% ± 7.7%, P < .05, ES 0.4-0.8) and sprint distance (32.3% ± 13.8% and 22.6% ± 11.2%, P < .05, ES 0.5-0.8). Technical indicators such as tackles (83.7% ± 42.3%), possessions won (47.2% ± 27.9%), and interceptions (59.1% ± 37.3%) illustrated substantial variability for attackers compared with all other positions (P < .05, ES 0.4-1.1). Central defenders demonstrated large variability for the number of times tackled per match (144.9% ± 58.3%) and passes attempted and received compared with other positions (39.2% ± 17.5% and 46.9% ± 20.2%, P < .001, ES 0.6-1.8). Contextual factors had limited impact on the variability of physical and technical parameters. Conclusions: The data demonstrate that technical parameters varied more from match to match than physical parameters. Defensive players (fullbacks and central defenders) displayed higher CVs for offensive technical variables, while attacking players (attackers and wide midfielders) exhibited higher CVs for defensive technical variables. Physical and technical performances are variable per se regardless of context.